A matrix of cognitive domains at the service of the metaphoric delegitimisation of politicians. (August 2017) - Pinero-Pinero, Gracia
Highlights: decoration, make-up, commerce, dream andfantasy domains delegitimise the politician. The conceptual mappings share the head metaphorthe politician is a fraudster . Conservative newspaper makes a greater use of these delegitimising domains. Abstract: Based on the triadic relationship that exists between discourse, cognition and society, this work analyses a matrix of cognitive domains that, through the mapping of metaphors, creates a delegitimising image of the politician. This matrix is composed of three conceptual frames that share the characteristic of presenting politicians as professionals in the art of lies, deceit and fraud: the first, decoration ormake-up, identifies the world of politics with actions aimed at decorating, adorning or embroidering reality in order to conceal its true nature; the second scenario, commerce, interprets the topic in question as a market of low value in which the retailer, the politician, makes use of often opaque strategies in order to camouflage their product and make it look like something which it is not; the matrix is completed by the frameworkdream orfantasy, which portrays the politician as a person who adorns, covers up or ignores the things that they do not wish to see, spuriously creating alternative worlds that respond to their own interests. Drawing on a corpus made up of political opinion articles taken from the most widely-distributed Spanish newspapers, we analyse the metaphoric correspondences established between the conceptual structures that these focus yield, and the topic studied.